2021
DOI: 10.1111/ijcp.14482
|View full text |Cite
|
Sign up to set email alerts
|

Outcome predictors of platelet‐rich plasma injection for moderate carpal tunnel syndrome

Abstract: Carpal tunnel syndrome (CTS), resulting from the entrapment of the median nerve (MN) in the carpal tunnel, is the most common peripheral entrapment neuropathy. It may cause numbness, tingling, and pain in the hand, especially in the thumb and first three fingers.Weakness and atrophy of the thenar muscle may be observed in severe cases and further results in disability in daily life activities. 1 The management of CTS is either through conservative or surgical treatment. Conservative treatment is recommended fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Several predictive factors that might influence the clinical efficacy of PRP treatment including age and different PRP concentration have been reported. However, it remains controversial depending on different disease nature ( Gentile and Garcovich, 2020 ; Alessio-Mazzola et al, 2021 ; Shen et al, 2021 ). In 60 cases of symptomatic knee osteoarthritis receiving homologous intra-articular PRP injections, a less favorable clinical outcome was reported in patients aged ≥ 80 years versus those age 65–79 years ( Bottegoni et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several predictive factors that might influence the clinical efficacy of PRP treatment including age and different PRP concentration have been reported. However, it remains controversial depending on different disease nature ( Gentile and Garcovich, 2020 ; Alessio-Mazzola et al, 2021 ; Shen et al, 2021 ). In 60 cases of symptomatic knee osteoarthritis receiving homologous intra-articular PRP injections, a less favorable clinical outcome was reported in patients aged ≥ 80 years versus those age 65–79 years ( Bottegoni et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its novelty, there is also little evidence on factors associated with failure of USTD. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Postprocedure physical therapy has been positively associated with USTD outcomes for LET, and body mass index, bodyweight, and severity have been found to be risk factors for PRP outcomes for other conditions. 12 , 14 , 15 There is a need for information on additional risk factors specific to outcomes in LET to assist in patient and physician decision making regarding the condition. The purpose of this study was to assess the efficacy of PRP and USTD while also studying patient characteristics as risk factors for treatment failure.…”
mentioning
confidence: 99%
“…The double-blind placebo-controlled study in 2021 had shown one-year efficacy of single-dose ultrasound-guided perineural injection with PRP in patients with moderate-to-severe CTS compared with NS injection [ 50 ]. Recently, Shen et al [ 51 ] revealed less body weight, decreased distal motor latency and CSA of the MN predict better outcome after perineural injection of PRP for moderate CTS in 3 to 6 months follow-up.…”
Section: Novel Motor-sparing Neural Injection For Ctsmentioning
confidence: 99%